IMPLEMENTASI AKAD IJARAH DALAM PRAKTIK SEWA MENYEWA TANAH PERTANIAN: ANALISIS PERSPEKTIF EKONOMI SYARIAH DI DESA MUNDUREJO, KABUPATEN JEMBER - Muftil Umam Ilham Zamzami; Syafi'i, Muhammad; Istikomah (LPPM Sekolah Tinggi Agama Islam Al-Utsmani Bondowoso, 2025)
This study discusses the practice of land leasing using the ijarah contract implemented by farmers in Mundurejo Village, Umbulsari District, Jember Regency. An interesting phenomenon in this research is that farmers lease vacant land to plant orange trees, which requires a relatively long period since orange trees take 2 to 3 years to begin producing fruit. The purpose of this study is to understand how the land leasing system is applied in Mundurejo Village and to examine its compliance with Islamic legal perspectives. This research uses a qualitative approach with a descriptive method. Data were collected through direct observation, interviews with parties involved in the leasing activities, and documentation of the leasing agreements used. The results show that the practice of land leasing in Mundurejo Village aligns with the principles of the ijarah contract in Islam. Farmers and landowners carry out written agreements that clearly state the object of the lease, the duration, the amount of ujrah (rental price), and terms related to land management. From the perspective of Islamic law, this practice is considered valid as it fulfills the pillars and conditions of ijarah and is based on fairness and mutual consent between the parties.